Impact Of Comprehensive Yoga Based Lifestyle Modification Program On Obesity And Linked Disorders - DR. ANITA CHOUDHARY; DR. PRABHAT KUMAR BUDHOLIA (International Journal of Pharma and Bio Sciences, 2015)
Obesity is a medical condition in which excess of body fat accumulates producing adverse effect on health, decreases life expectancy and increases health problem as a results of combination of lack of physical activity, high calories intake, endocrinal susceptibility, medication psychiatric illness etc leading to increase mortality by predisposing diseases like Heart Diseases, Type 2 diabetes, Breathing disorder during sleep, Cancer and Osteoarthritis. To prospectively assess the effect of comprehensive yoga based lifestyle modification program on obesity and to evaluate the influence of yoga in relieving symptoms of anxiety and depression. 62 female age group 25 to 45 age group who registered for obesity Yoga camp at Ujjain Yoga bhavan were enrolled in the study. All were evaluated by obesity clinical parameters (Skin fold thickness, Body mass index and Waist/ hip ratio) at the beginning of the study. Then under supervision of yoga experts they were made to follow prescribed Yoga routine and diet program of 4 weeks for 3 months. The obesity parameters were evaluated again at the end of study. In the present study the difference of score before and after interventions of yoga based life style modification showed significant decrease in the parameters of obesity in the study group, skin fold thickness (P < 0.05), Body mass index (P < 0.05) and Waist/hip ratio (P < 0.05). The results of the present study showed that Yoga based life style modification ( selected asanas and diet program) helps in decreasing body weight as Yogic life style include physical exercise, balanced diet and mental peace that helps in gaining positive attitude and calm disposition all are ingredients of good health.